Heat transfer on a hot surface impinged by a cold circular liquid jet - Shu, Jian Jun (2011)
The paper considers heat transfer characteristics of thin film flow over a hot horizontal flat plate resulting from a cold vertical jet of liquid falling onto the surface. A numerical solution of high accuracy is obtained for large Reynolds numbers using the